The Difference in Repeatability of Automated Superficial Retinal Vessel Density according to the Measurement Area Using OCT Angiography - Hyung Bin Lim; Tae Seen Kang; Yeo Kyoung Won; Jung Yeul Kim (Journal of Ophthalmology)
Purpose. To evaluate the difference in the repeatability of automated superficial retinal vessel density and foveal avascular zone (FAZ) metrics according to the measurement area of optical coherence tomography angiography (OCTA). Methods. A total of 127 normal eyes from 127 healthy subjects were included. Macular angiography images were acquired from all subjects using the Zeiss Cirrus 5000 with AngioPlex™ OCTA software. Scans of 3 × 3 mm and 6 × 6 mm were each performed twice in a randomly arranged sequence. Vessel density (VD), perfusion density (PD), and FAZ metrics of the superficial capillary plexus were calculated automatically for all scans, and the repeatabilities for both scan patterns were assessed based on intraclass correlation (ICC), coefficient of variation (CV), and coefficient of repeatability (CR) parameters. The average measured values in the two scan patterns were also compared. Results. VD was significantly greater in the 3 × 3 mm scan than in the 6 × 6 mm scan according to all parameters, whereas PD was significantly less in the 3 × 3 mm scan than in the 6 × 6 mm scan. The ICCs for VDs in the central fovea were 0.826 and 0.741 for the 3 × 3 and 6 × 6 mm scans, respectively, and the CVs were 8.00% and 12.75%. For PDs, the ICCs were 0.839 and 0.762 and the CVs were 9.32% and 14.90%. The FAZ metrics in the 3 × 3 mm scan showed good repeatability with an ICC >0.75 and a CV <10.0%. However, all ICCs for the 6 × 6 mm scans were <0.75, and the CVs were all >10%. Conclusions. The 6 × 6 mm macular angiography scans resulted in lower repeatabilities than the 3 × 3 mm scans according to all OCTA parameters, particularly in the central fovea and FAZ metrics. The 3 × 3 mm scan was more suitable than the 6 × 6 mm scan for analyzing macular microvascular density and FAZ metrics.